Relationship between value chain governance and value chain integration (as an outcome of a public private partnership to promote value chain competiveness at the regional level). The case of the value chain cotton/textile/clothing in Tolima (Colombia) - Alexander Blandon Lopez; Janeth Gonzalez Rubio (European Regional Science Association (ERSA), 2016)
Relationship between value chain governance and value chain integration (as an outcome of a public private partnership to promote value chain competiveness at the regional level). The case of the rice value chain in Tolima (Colombia) Alexander Blandón López PhD. Lecturer Universidad del Tolima Janeth González Rubio MA Lecturer Universidad del Tolima This paper focuses on the study of the relationship between value chain governance and value chain integration (as an outcome of a public private partnership to promote value chain competiveness at the regional level). The study expands and disaggregates Gereffi's Global Commodity Chain framework and applies some of its analytical categories (input output structure and governance amongst others) to the study of regional value chains. The governance structure embodies the 'authority and power relations that determine how financial, material, and human resources are allocated and flow within the chain' (Gereffi 1994: 97). In this sense, the concept relates to the 'power relations in the chain and the institutions which mould and wield this power' (Kaplinsky and Morris 2000). There is a directed network form of coordination of the rice value chain. Historically there had been developed systems of formal and informal agreements between producers and rice threshing entrepreneurs on subjects such as payments, rice varieties and quantities. Other forms of coordination such as support strategies for rice producers, supply of packing inputs, financing and technical assistance have also been developed (Corpoica 2000: 54). These practices provided a basic common ground for the discussion and signing of the competitiveness agreement as an instrument of coordination for the value chain rice threshing in Tolima (Colombia). From a governance point of view, it can be stated that a domestic oligopsony of an agricultural raw material protected by the national government reduces the likelihood of success for the expected developmental outcomes of a competitiveness agreement. A domestic market protected from imports introduces as a main contention point between agro-producers and industrialists in a competitiveness agreement the issue of price determination. At the end, the government has to arbitrate. Finally, a competitiveness agreement embodies for a regional government a potential instrument for social and economic policy interventions. First, governments can participate in this scheme, having in mind the promotion of social policies (employment generation and smallholder income improvements), particularly in depressed areas with a tradition or a potential for raw material production. Second, competitiveness agreements offer to the public sector a scope of action to deal with regional economic restructuring processes and to promote endogenous development policies with active involvement and contribution of several regional stakeholders Blandon, L.A (2012) Economic restructuring and value chains. The search for regional competitiveness in Colombia. PHD thesis. Institute of Social Studies of Erasmus University Rotterdam
Keywords: O25; O38; 330; Governance; value chain; rice; Competitiveness agreement